Look Out before Polypectomy in Patients with Diverticular Disease – A Case of a Large, Inverted Diverticulum of the Colon Resembling a Pedunculated Polyp - Omero Alessandro Paoluzi; Claudio Tosti; Fabio Andrei; Italo Stroppa; Francesco Pallone (Canadian Journal of Gastroenterology)
Diverticular disease of the colon may be responsible for abdominal symptoms requiring colonoscopy, which may reveal the presence of concomitant polyps. A polyp found during colonoscopy in patients with colonic diverticular disease may be removed by endoscopic polypectomy with electrosurgical snare, a procedure associated with an incidence of perforation of less than 0.05%. The risk of such a complication may be higher in the event of an inverted colonic diverticulum, which may be misinterpreted as a polypoid lesion at colonoscopy. To date, fewer than 20 cases of inverted colonic diverticula, diagnosed at colonoscopy or following air contrast barium enema, have been reported in the literature. The present report describes a 68-year-old woman who underwent a screening colonoscopy, which revealed a voluminous pedunculated polyp that was recognized to be an inverted giant colonic diverticulum before endoscopic polypectomy.